Women and Small Business: Contributing to Household income and Family wellbeing - Iji, Mary Eru; Ebong, Edem A.; Omang, Thomas A.; Ojong-Ejoh, Mary U. (Quantitative Economics and Management Studies, 2021)
The objective of the study is to examine the extent to which women involvement is small business contributes to household income and family wellbeing. The study adopted the survey research method in collecting data from 317 women from Yala Local Government Area of Cross River State, Nigeria using Cluster and Purposive sampling technique. The Survey Monkey Sample Determinant Technique was used to determine the sample size for the study. The instrument of data collection was a semi-structured self-developed questionnaire. Data collected from the Field was analyzed using descriptive statistic and parametric statistic (Simple Lineal Regression) at 0.05 level of significance. The result from the descriptive statistics revealed that most of the women used in the study, 97.41 per cent do not depend solely on their husband income. 63.70 cent of women spend all the money from their endeavour in taking care of their homes. 81.10 per cent of the women reported that they are able to contribute to the household and take care of themselves. From the parametric statistics carried out, result revealed a significant correlation between women involved in small business and household income and family wellbeing in Yala. The study thereby concludes that women in small business significantly contribute to household income and family wellbeing. The study calls for governmental effort towards improving the capacity of women in Yala through self-help programs and microcredit.